2018
DOI: 10.1017/jfm.2018.331
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of heat transfer from a cylinder immersed in the production and decay regions of grid-element turbulence

Abstract: The present direct numerical simulation (DNS) study, the first of its kind, explores the effect that the location of a cylinder, immersed in the turbulent wake of a grid-element, has on heat transfer. An insulated single square grid-element is used to generate the turbulent wake upstream of the heated circular cylinder. Due to fine-scale resolution requirements, the simulations are carried out for a low Reynolds number. Three locations downstream of the grid-element, inside the production, peak and decay regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
(102 reference statements)
1
6
0
Order By: Relevance
“…Besides, the fractal induced velocity fluctuations at several locations within ( X / X * = 0.12) and after ( X / X * = 0.25) the fin array are found to be strongly non-Gaussian. These two observations are consonant with the earlier studies, where velocity fluctuations are Gaussian at X / X * < 0.1 but highly non-Gaussian between 0.1 < X / X * < 0.26 24 , 38 , 42 , 78 , 84 . Remarkably, the gaussianity behaviour leeward of SFG (0.12 < X / X * < 0.25) is highly local position-dependent.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Besides, the fractal induced velocity fluctuations at several locations within ( X / X * = 0.12) and after ( X / X * = 0.25) the fin array are found to be strongly non-Gaussian. These two observations are consonant with the earlier studies, where velocity fluctuations are Gaussian at X / X * < 0.1 but highly non-Gaussian between 0.1 < X / X * < 0.26 24 , 38 , 42 , 78 , 84 . Remarkably, the gaussianity behaviour leeward of SFG (0.12 < X / X * < 0.25) is highly local position-dependent.…”
Section: Resultssupporting
confidence: 91%
“…Previous researchers 24 , 38 , 42 , 78 , 84 have extensively observed that immediately leeward of fractal insert ( X / X * < 0.1), the channel centreline velocity fluctuations are Gaussian with skewness of zero and flatness of 3. As the flow travels further downstream (0.1 < X / X * < 0.26), the velocity fluctuations appear to be strongly non-Gaussian, with the largest negative values of skewness and the largest positive values of flatness occurring at X / X *≈0.2.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The code is parallelized using the PETSc libraries [47]. More details about the solver can be found in Paul et al [37], Paul [48], Paul et al [49,50].…”
Section: Numerical Methods and Computational Parametersmentioning
confidence: 99%